The Application of International Human Rights and International Humanitarian Laws in Armed Conflict: Appraisal of the Armed Conflict in Anglophone Cameroon - Prof. Mikano E. Kiye; Dr. Molua Patrick Ewange (Studies in Law and Justice, 2025)
Cameroon has been projected as a peaceful country since achieving independence in 1960. However, since late 2017, an armed conflict broke out in the Anglophone regions of the country following the government’s brutal repression of the protests of lawyers, teachers, and University of Buea students in late 2016, and subsequently in September and October 2017 with the violent clampdown of the general protests in Anglophone Cameroon. The violence of the armed conflict has led to several thousands of deaths, several hundred of villages razed, hundreds of internally displaced persons and refugees in neighboring Nigeria. According to analysts, there has been an unprecedented violation of human rights and humanitarian laws by the belligerents in their conduct of hostilities, with devastating consequences on the civilian population, in total disregard of international norms. To this end, this paper examines the violations of human rights and humanitarian laws recorded in the conflict-torn Anglophone regions of Cameroon and assesses the obligations of the belligerents, the defense and security forces of the state on the one part and the Anglophone armed separatist groups on the other, to respect these norms during the prosecution of the war in the country.